Qualidade de vida de pacientes operados por câncer do aparelho gastrointestinal - Tartuce, Luciana Marya Gusmão (2016)
The changing profile of morbidity and mortality points to an increase in both life expectancy of human beings and the growing prevalence of chronic degenerative diseases, such as cancer. Regarding the impact that both diagnosis and treatment, especially, surgical one, have on patients, their families, and social environment, it is worth caring about the overall health (OH) and Quality of Life (QOL) as perceived by the individual. The main objective of this study was to assess health-related QOL among patients undergoing surgeries for gastrointestinal cancer who were treated in a surgery clinic of a school hospital. It is a descriptive exploratory quantitative study, carried out with 31 patients, mostly women, from the capital of Goiás, aged between 60 and 69 years old, catholic, married, retired, with elementary level of education, predominantly diagnosed with colorectal cancer, all of them treated at the Surgery Clinic of the HC/UFG. The instruments used were: Socio-demographic Questionnaire, QSG, WHOQOL-bref and EORTC QLQ-C30. The socio-demographic data and diagnosis were assessed regarding its frequency and average. The WHOQOL-bref, EORTC QLQ-C30 and QSG were assessed according to their manuals and guidelines. The data collected was organized in the SPSS 18.0 statistical program. The quality of life was considered to be regular in two moments (30 and 60 postoperative days), being the Physical domain the most affected. As for the overall health, the QSG showed some effect in the sleep disturbance factor in the 30-day assessment, and in the 60-day assessment all factors were considered normal. The correlation between the factors of OH and the EORTC QOL scores C-30 showed positive and significant impact in all dimensions: the better overall health, the better QOL. However, in the correlation of the OH and the QOL assessed through the WHOQOL-Bref, there was only significant and positive correlation between OH and the Physical Dimensions and the environment. It is concluded that assessing the QOL of sick people is a complex process due to the characteristics of subjectivity and multidimensionality involved, making it necessary the use of valid and reliable instruments. The surgical procedure has brought benefits to the participants of this study, however qualitative methodologies could be added to the understanding of the meanings as assigned by the sick people, with similar experiences of cancer treatment, to several factors of their QOL and their OH, throughout the follow-up. Thus, the evaluation of the perception of QOL and the OH can be inserted in clinical practice and regular care of sick people.